PIENNO-MOASH: Formulation of Nanoparticle Mouthwash from Pineapple Peel Extract (Ananas comosus L.) as an Antibacterial Agent Against Streptococcus mutans via In Silico and In Vitro Studies - Fayyadh, Achmad; Ferya, Fachri; Fitriana, Aiza (CV. Publikasi Indonesia, 2025)
Dental caries cases are an increasing problem in adult and pediatric patients, one of the causes of which is the Streptococcus mutans bacteria. Pineapple peel (Ananas comosus L.) is a plant part that has been known to have antibacterial activity due to the content of secondary metabolites epicatechin and quercetin. However, the exploration of pineapple peel as a nanoparticle mouthwash has not been widely done. This study aims to extract pineapple peel, analyze the phytochemical profile of the extract, conduct molecular docking tests on dental caries protein targets, test the antibacterial activity of pineapple peel extract on Streptococcus mutans cultures, optimize and evaluate the formulation of